Characterization of SPATA5‐related encephalopathy in early childhood. Issue 5 (4th July 2016) - Kurata, H.; Terashima, H.; Nakashima, M.; Okazaki, T.; Matsumura, W.; Ohno, K.; Saito, Y.; Maegaki, Y.; Kubota, M.; Nanba, E.; Saitsu, H.; Matsumoto, N.; et al.
Abstract : Mutations in SPATA5 have recently been shown to result in a phenotype of microcephaly, intellectual disability, seizures, and hearing loss in childhood. Our aim in this report is to delineate the SPATA5 syndrome as a clinical entity, including the facial appearance, neurophysiological, and neuroimaging findings. Using whole‐exome sequencing and Sanger sequencing, we identified three children with SPATA5 mutations from two families. Two siblings carried compound heterozygous mutations, c.989_991del (p.Thr330del) and c.2130_2133del (p.Glu711Profs*21), and the third child had c.967T>A (p.Phe323Ile) and c.2146G>C (p.Ala716Pro) mutations. The three patients manifested microcephaly, psychomotor retardation, hypotonus or hypertonus, and bilateral hearing loss from early infancy. Common facies were a depressed nasal bridge/ridge, broad eyebrows, and retrognathia. Epileptic spasms or tonic seizures emerged at 6–12 months of age. Interictal electroencephalography showed multifocal spikes and bursts of asynchronous diffuse spike‐wave complexes. Augmented amplitudes of visually evoked potentials were detected in two patients. Magnetic resonance imaging revealed hypomyelination, thin corpus callosum, and progressive cerebral atrophy. Blood copper levels were also elevated or close to the upper normal levels in these children. Clinical delineation of the SPATA5 ‐related encephalopathy should improve diagnosis, facilitating further clinical and molecular investigation. Abstract : Absence of brainstem auditory evoked potentials and augmented visually evoked potentials, hypomyelination and progressive cerebral atrophy, as well as decreased choline and increased lactate peaks observed in STATA5‐related encephalopathy.